The effect of topical application of meloxicam on inflamed dental pulp - Jing-Yi Li; Sai-Nan Wang; Yan-Mei Dong (Elsevier, 2021)
Background/purpose: Effective regulation of the inflammatory process is essential for pulp repair and regeneration. Meloxicam has anti-inflammatory activity in systemic administration. The purpose of this study is to observe effects of topically applied meloxicam on inflamed pulp and to explore its potential value in the treatment of pulpitis. Materials and methods: The coronal pulp tissues of rat molars were stimulated with 10 mg/mL lipopolysaccharide (LPS group) and then treated with 500 μmol/L meloxicam (meloxicam group). The untreated pulp tissues were used as the control group. After 3 h of incubation in vitro, the gene expression of interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α) in each group was detected by real-time RT-PCR. The pulp tissues of each group were randomly subcutaneously implanted into nude mice, and 500 μmol/L meloxicam was injected into the subcutaneous pocket of the meloxicam group. Haematoxylin eosin staining, Masson staining and immunohistochemical staining were performed on samples after 3 days and 4 weeks retrieval, respectively. Results: Compared with the LPS group, the mRNA expression levels of TNF-α and IL-6 of the meloxicam group were significantly reduced in vitro. The inflammatory response and cyclooxygenase-2 expression of the meloxicam group were decreased, and osteodentin-like tissue was generated in the pulp cross section of the meloxicam group in vivo. Conclusion: The topical application of meloxicam inhibits the inflammatory response of inflamed pulp and further promotes the formation of osteodentin-like tissues but fails to induce the formation of the pulp-dentin complex. Topically applied meloxicam has the potential to regulate pulp inflammation.